Diagnostic Validity of Leucocyte Esterase Dipstick Tests for Spontaneous Bacterial Peritonitis in Patients with Cirrhosis - Muhammad Kamran Hassan, Wiqas Ahmad, Muhammad Kashif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the worst sequelae of cirrhosis and ascites is spontaneous bacterial peritonitis (SBP). Early detection and treatment of SBP are therefore essential for survival because this complication is linked to a high death risk if antibiotics are not administered promptly. Leukocyte esterase dipstick testing can identify the SBP quickly. Objective: To evaluate the diagnostic accuracy of leucocyte esterase dipstick test for the detection of spontaneous bacterial peritonitis taking ascitic fluid neutrophil count as gold standard. Study Design: Cross Sectional Study Settings: Department of Gastroenterology, Lady Reading Hospital, Peshawar Study Duration: This study was conducted from 1st July 2021 till 30th June 2022 Materials and Methods: Two samples (10cc each) of ascitic fluid aspirate were obtained from patients with cirrhosis on admission to the hospital, presenting with ascites, fever and abdominal pain. Bedside leucocyte esterase dipstick test was performed on one sample and the other was sent to hospital laboratory for ascitic fluid analysis for neutrophil count. The results of both modalities were compared diagnostic accuracy which was recorded in terms of sensitivity, specificity, positive predictive value and negative predictive. Results: Mean age of the patients was 46.68 ± 10.239 years. A total of 170 patients were enrolled. Age of the patients ranged from 18 to 75 years. Male patients were 113 (66.5%) while 57 patients (33.5%) were female. Hepatitis C was the leading cause of cirrhosis observed in 89 patients (52.4%). The sensitivity, specificity, positive and negative predictive value of leucocyte esterase dipstick test observed were 89.7%, 96.2%, 87.5% and 96.9% respectively. Conclusion: Leucocyte esterase dipstick test is a convenient, inexpensive and rapid diagnostic modality for SBP with better diagnostic accuracy. Keywords: Spontaneous Bacterial Peritonitis, Leucocyte Esterase Dipstick test, Diagnostic Accuracy.